IMPACT OF GOVERNMENT POLICIES AND LICENSING ON THE ECONOMIC STABILITY OF STREET VENDORS (SVs) - Dipali V. Soitkar; Sanjay S. Tekade (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looks into how licensing and governmental regulations affect the financial stability of street sellers in Nagpur. Through the use of structured questionnaires and a descriptive study approach, 150 street vendors provided primary data. According to the report, licensed merchants have greater access to governmental financial programs like the PM SVANidhi loan and earn noticeably higher salaries. However, a sizable percentage of vendors are not aware of pertinent laws and do not have proper licenses, which restricts their capacity to take advantage of these programs. The favourable correlation between license, policy knowledge, and economic consequences is confirmed by t-tests and chi-square tests. In order to promote the sustainable existence of street vendors in urban environments, the study emphasises the necessity of better policy outreach, streamlined licensing procedures, and strengthened support systems.